QE in a quasi-preferred habitat: The case of the Danish pension sector and the ECB asset purchase programme - Søren Lejsgaard Autrup; Jakob Roager Jensen (Danmarks Nationalbank, 2021)
The portfolio rebalancing of Danish pension companies following the introduction of the ECB's asset purchase programmes is studied using a new and unique data set of their financial transactions and holdings since 2015. Due to a long-standing fixed exchange rate regime, Danish pension companies own large amounts of bonds eligible for purchase in ECB's programmes. This allows us to study cross-border spillovers in a fixed exchange rate regime from central banks' asset purchases. We document that pension companies reduced their demand for bonds eligible for ECB's asset purchases and increased their demand for Danish bonds in the first months after the beginning of ECB asset purchases in March 2015. However, the changes in bond demand disappeared after the initial phase of the ECB purchase programmes. We also show that pension companies act differently depending on the type of obligations to their pension plan holders. Companies without strictly binding guarantees to pension plan holders sold German government bonds, but increased their holdings of other bonds eligible for ECB purchases. Companies with strict guarantees to the pension plan holders reduced their demand for bonds eligible for ECB purchases initially, but increased their holdings of these bonds while ECB purchases were still ongoing at a high pace. Overall, our findings show that Danish pension funds, especially those with guaranteed obligations, can be considered having a quasi-preferred habitat in euro.
Keywords: E52; E42; E58; G10; G15; G22; 330; Monetary policy; Monetary-policy transmission; Capital flows; Financial assets